Decarboxylative Propargylation/Hydroamination/Aromatization Enabled by Copper/Amine Cooperative Catalysis: Construction of Cyclopenta[b]indole Derivatives - Xiong, Jiale; Zhao, Xiaoyun; Feng, Xing; Xianxing, Jiang (Current Organic Chemistry, 2020)
An efficient decarboxylative cycloaddition of 2,3-dioxopyrrolidines and ethynyl benzoxazinanones has been established by cooperative copper/amine catalysis. A copper– allenylidene complex and enolate intermediate, each catalytically generated from distinct substrates, underwent a cascade propargylation/hydroamination/aromatization process to construct a big library of cyclopenta[b]indole derivatives with good to excellent yields and excellent diastereoselectivity.
Keywords: Cooperative catalysis